1992
DOI: 10.1111/j.1747-5457.1992.tb00959.x
|View full text |Cite
|
Sign up to set email alerts
|

The Red Sea — Gulf of Aden: Biostratigraphy, Lithostratigraphy and Palaeoenvironments

Abstract: Sediments of Palaeozoic, Mesozoic and early Palaeogene ages experienced a similar geological history in Ethiopia, Yemen and Somalia. During the late Eocene, however, uplift and differential erosion took place, prior to rift development in the middle Oligocene, when the proto‐Gulf of Aden became established. To a certain extent, a similar sequence of events had also taken place in those regions of Egypt, Sudan, Ethiopia, Yemen and Saudi Arabia which border the Red Sea, but post‐Eocene subsidence is now believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 15 publications
(1 reference statement)
2
56
0
Order By: Relevance
“…Offshore from the Hadhramaut region, maxima of about 2000 m and 1100 m of the syn-rift Shihr Group and post-rift Sarar Formation, respectively, were encountered in six exploratory wells (Haitham and Nani, 1990;Bott et al, 1992;Hughes and Beydoun, 1992). Thinner sections of the same age were seen in the two wells drilled offshore central Somalia (Fig.…”
Section: Syn-to Post-rift Depositionmentioning
confidence: 90%
See 1 more Smart Citation
“…Offshore from the Hadhramaut region, maxima of about 2000 m and 1100 m of the syn-rift Shihr Group and post-rift Sarar Formation, respectively, were encountered in six exploratory wells (Haitham and Nani, 1990;Bott et al, 1992;Hughes and Beydoun, 1992). Thinner sections of the same age were seen in the two wells drilled offshore central Somalia (Fig.…”
Section: Syn-to Post-rift Depositionmentioning
confidence: 90%
“…Cretaceous volcanic units have been encountered below the Mukawar Formation in offshore wells ( Fig. 9; Hughes and Beydoun, 1992).…”
Section: Pre-rift Stratigraphy and Proto-red Sea Embaymentsmentioning
confidence: 98%
“…The Gulf of Aden rift system propagated from the Alula/Ra's Fartaq trend in the east to the Bab Al-Mandab in the west, and thus joined the Owen fracture zone to the Afar hotspot (Courtillot 1980;Fournier et al 2010;Leroy et al 2004;Manighetti et al 1998). The Red Sea rifting propagated from south to north, joining the Dead Sea and Levant strike-slip fault (Bott et al 1992;Hughes et al 1991;Hughes and Beydoun 1992). The Red Sea was cut off from India Ocean via Bab Al-Mandab in the late Middle Miocene, giving rise to thick evaporite deposition in the Red Sea during this time.…”
Section: Cenozoic Basinsmentioning
confidence: 99%
“…There have been long running debates about the ages of these units and where precisely to place the base-rift unconformity. Micropaleontological studies of exploratory wells and some outcrops have suggested that the oldest syn-rift formations, exclusive of the very southern Red Sea, are ϳ23 Ma, near the Oligocene-Miocene boundary (Bunter and Abdel Magid 1989;Hughes and Beydoun 1992;McClay et al 1998;Bosworth et al 1998;Hughes et al 1999). Other interpretations have placed the base syn-rift unconformity within the Late Oligocene (Dullo et al 1983;Bayer et al 1988;Purser and Hötzl 1988;El Barkooky and El-Araby 1999;Bosworth and McClay 2001;Jackson et al 2006;Jackson 2008), or even Early Oligocene (Hughes and Filatoff 1995;Koeshidayatullah et al 2016).…”
Section: Late Oligocene -Early Miocene Structuration and Syn-rift Depmentioning
confidence: 99%